Accounting Data Integration Challenges in Local Government Information System Implementation: A Qualitative Case Study of the North Toraja Transportation Service - Patanggung, Rika Teko'; Igelia; Reme, Novita; Roreng, Petrus Peleng; Danduru, Beatrix Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This study investigates the accounting data integration challenges encountered during the implementation of the Local Government Information System (SIPD) at the North Toraja Transportation Service. The research specifically examines issues that hinder the integration process, including inconsistencies in Financial Accounting and Reporting (AKLAP) features within SIPD, technical limitations, human resource constraints, and financial barriers. Using a qualitative descriptive approach through a case study conducted starting in September 2025, data were collected through interviews, observations, and documentation. The findings reveal that the primary challenges include the incompatibility between SIPD features and existing operational procedures, technical disruptions such as unstable system connectivity, limited staffing capacity, and insufficient budgeting. This study further proposes practical recommendations, including human resource training, enhancement of SIPD functional features, and transitional integration of manual systems to strengthen reporting efficiency, financial accountability, and transparency within local government operations.